حماية اليتيم في الشريعة الإسلامية والقوانين الوضعية - قرقب إسمهان (جامعة محمد بوضياف المسيلة, 2019)
من أجل خطوة تجاه اليتيم تأتي هذه الدراسة لتعالج موضوعا متعلقا بحماية اليتيم في الشريعة الاسلامية والقوانين الوضعية. ان حماية اليتيم حق تفرضه الفطرة، وتحفظه الغريزة لذلك كفلت الشريعة الإسلامية والقوانين الوضعية لحمايته، غير أن الشريعة شاملة كاملة في بسط كل أنواع الحماية الواجب إحاطتها باليتيم، وأوجبت عقوبات عمن يتساهل ويقلل من شأنها، على عكس القوانين الوضعية يمكن القول بأنها لا تغطى بصفة كاملة كل مجالات الحماية لحقوقه رغم الجهود المستمرة فهي صورية وشعارات فقط، بل لابد من توفر آليات فعلية لتوفير الحماية اللازمة. الكلمات المفتاحية: اليتيم - الشريعة الاسلامية – القوانين الوضعية – الحماية الجزائية-الحماية المدنية Abstract: As a step towards the orphan, this study deals with a topic related to the protection of the orphan in Islamic law and the Status laws. The protection of the orphan is a right imposed by nature, and reserved by instinct, guaranteed by Islamic law and status laws to protect it. However, the Shari'a is full comprehensive in extending all kinds of protection that must for the orphans, and penalties are imposed on those who tolerate and minimize them. Contrary to statutes, it can be said that they do not fully cover all areas of protection of his rights. Despite the ongoing efforts, it is only slogans, so there must be an effective mechanisms to provide the necessary protection. Keywords: Orphan-Islamic law-status laws-penal protection-civil protection
Keywords: : اليتيم - الشريعة الاسلامية – القوانين الوضعية – الحماية الجزائية-الحماية المدنية